Assessing Indonesia’s Social Forestry Achievements within the Enhanced Nationally Determined Contribution (ENDC) Framework - Maulana, Bangkit; Sjah, Taslim; Budastra, Ketut (Jurnal Biologi Tropis, 2026)
Global climate change demands concrete commitment from every country to reduce greenhouse gas emissions. Indonesia established Enhanced Nationally Determined Contribution with emission reduction targets of 31.89% unconditionally and 43.20% conditionally by 2030, with Forest and Other Land Use sector as key to achieving Net Sink 2030. Social Forestry program plays strategic role but faces complex challenges related to community capacity, institutional coordination, and regulatory alignment. This study analyzes position and contribution of Social Forestry toward Enhanced Nationally Determined Contribution achievement using Systematic Literature Review of 25 publications from 2020-2025. Secondary data from policy documents and official reports were analyzed using DPSIR Framework approach. Results show Social Forestry program until 2024 covers 8.02 million hectares of 12.7 million hectares target with carbon stock reaching 110.5 million tons CO2eq and potential contribution of 34.6% toward forestry sector emission reduction target. Program successfully reduced deforestation rate to lowest level in 20 years at 115,459 hectares in 2019-2020. Main challenges include limited community capacity, excessive administrative burden, weak coordination, and regulatory misalignment. Optimization requires capacity strengthening, procedure simplification, effective coordination, regulatory synchronization, and integration with carbon economic value schemes to achieve Forest and Other Land Use Net Sink 2030.